Photodynamic therapy corrects abnormal cancer-associated gene expression observed in actinic keratosis lesions and induces a remodeling effect in photodamaged skin. Issue 2 (August 2018) - Joly, Florence; Deret, Sophie; Gamboa, Bastien; Menigot, Corinne; Fogel, Paul; Mounier, Carine; Reiniche, Pascale; Sidou, Farzaneh; Aubert, Jérome; Lear, John; Fryer, Anthony A.; Zolezzi, Francesca; et al.
Highlights: MAL-PDT corrects abnormally expressed cancer-associated genes in actinic keratosis. MAL-PDT normalizes cell cycle-related genes in actinic keratosis. MAL-PDT at gene expression level indicates a remodeling effect on photodamaged skin. Abstract: Background: Actinic keratoses (AK) are proliferations of neoplastic keratinocytes in the epidermis resulting from cumulative exposure to ultraviolet radiation (UVR), which are liable to transform into squamous cell carcinoma (SCC). Organ Transplant Recipients (OTR) have an increased risk of developing SCC as a consequence of long-term immunosuppressive therapy. The aim of this study was to determine the molecular signature of AKs from OTR prior to treatment with methyl aminolevulinate-photodynamic therapy (MAL-PDT), and to assess what impact the treatment has on promoting remodeling of the photo-damaged skin. Methods: Seven patients were enrolled on a clinical trial to assess the effect of MAL-PDT with biopsies taken at screening prior to the first treatment session (week 1), and six weeks after completion of final treatment (week 18). Whole-genome gene expression analysis was carried out on skin biopsies isolated from an AK lesion, an area surrounding the lesion, and a non-sun exposed region of the body. Quantitative PCR was utilized to confirm the differential expression of key genes. Results: MAL-PDT treatment corrected abnormal proliferation-related gene profiles, corrected aberrantly expressed cancer-associated genes and induced expression of dermal extracellular matrix genes in photo-exposed skin. Conclusion: The efficacy of the MAL-PDT on AK lesions was confirmed at whole-genome gene expression level. A transcriptional signature of remodeling, identified through assessing the effect of MAL-PDT on photodamaged skin, supports the use of MAL-PDT for treating photodamaged skin and field cancerized areas.